Speech Development and Communicative Demands in Autistic Children Using the Picture Exchange Communication System (PECS) - Faiza Arshad, Sidra Ansar, Rabia Khalid, Mahrukh Rashid, Fahad Masood, Kanza Sana Umer (Pakistan Journal of Medical & Health Sciences, 2023)
Background: PECS, or Picture Exchange Communication System, addressed in writing. The answers for such schemes to influence word retrieval in autism spectrum disorders in children (ASD). Objective: The objective of the current study finding out the effects of Development of the picture exchange communication system in autistic children’s speech and communicative requesting was the main goal of the current study. Materials & Methods: The study design was Qusai experimental. The research was carried out at Riphah International University Lahore campus. Data was collected from Lahore. The study time was six months after the approval of synopsis. Data was collected from the Autistic children and purposive sampling technique was used in this research. The sample size calculated was ten. The picture-exchange technique for communication (PECS) was used for data collection. Data was examined using SPSS software and Endnotes were used for references. Results: Results from the Childhood Autism Rating Scale (CARS) assessment scoring form indicated that there is a significant relationship between the Effects of Communicative PECS speech and request development in autistic children, overall analysis of the pre and post scores of CARS assessment. In which mean of pre score is 36.15 and mean of post score is 29.5. The standard deviation of pre score is 8.47 and the post score standard deviation is 5.39. The mean difference showed the improvement between CARS pre and post assessment. Used was the paired sample t test for finding the mean difference between the pre and post scores. The results indicate that every participant showed improvement in different skills such as verbal and nonverbal communication, visual response. Some participants got higher in verbal communication Practical implication: This will give us a better understanding of how speech develops in children with autism and how children’s vocabulary develops and awareness develops in children. Conclusion: The pre-post assessment of The Childhood Autism Rating scale (CARS) with intervention of PECS concluded that there is significant influence of intervention using a photo exchange communication technology for autistic kids. Keywords: Autism, Chemical Imbalance, PECS, CARS, Autism Rating Scale, Autism spectrum condition